Losing streak : how Tasmania was gamed by the gambling industry - Boyce, James (Historian) (Black Inc., 2017)
A jaw-dropping account of how one company came to own every poker machine in the state of Tasmania - and the cost to democracy, the public purse and problem gamblers and their families. -- -- Losing Streak James Boyce is the acclaimed author of Van Diemen's Land, 1835 and Born Bad. His books have been shortlisted for almost every major Australian literary award and he has won the Tasmania Book Prize on two occasions. He is also a professional social worker, who worked for many years in social policy and research and has been involved in the poker-machine debate for nearly twenty years.